The Effect of Blended Learning on Self-Control and Time Management in Students at MAN 1 Makassar in Biology Learning - Mutmainna, Andi Mutia; Hiola, St. Fatmah; Muis, Abd. (Universitas Negeri Makassar, 2025)
Abstract. This study aims to determine the effect of blended learning on self-control and time management in learning among students at MAN 1 Makassar in biology lessons. This research was conducted in the odd semester of the 2024/2025 academic year using a quasi-experimental method with a pretest-posttest experimental control group design. The research sample consisted of two groups, namely the experimental group, which was taught using blended learning, and the control group, which was taught without blended learning. The research instrument was a non-test instrument in the form of a closed questionnaire to assess the level of self-control and time management of students' learning. The data obtained was analyzed using the Statistical Package for Social Science (SPSS). The results show that there is a significant difference between the experimental group and the control group in terms of students' self-control and learning time management, based on the average self-control scores of the experimental class 48.00 and the control class 39.25 and the average learning time management scores of the experimental class 48,13 and the control class 37,36. The conclusion of this study, that is the application of blended learning has an effect on improving students' self-control and time management in learning Biology.Keywords: Blended learning, self-control, time management.